PENGARUH RASIO KEUANGAN TERHADAP INVESTMENT OPPORTUNITY SET (IOS) DALAM TAHAPAN SIKLUS KEHIDUPAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2008-2010 - CHANDRA, ELVIA (: 2303-1719)
The company's goal is to invest in the hope of gaining advantage in the future so that companies can be said to be growing. Investment choices made in the future the company is then known as the Investment Opportunity Set (IOS). Many of the indicators that can effect IOS, one of which is financial ratios. The concept of corporate life cycle can be used to describe the performance measures in the form of financial ratios and growth of the company. This study aims to analyze the effect of liquidity ratios, profitability, activity, and solvency of the Investment Opportunity Set (IOS)in the stage of the life cycle of manufacturing companies listed on Indonesia Stock Exchange in the period 2008-2010. The study design used was a quantitative study with the hypothesis. Independent variables in the form of liquidity, profitability, activity, and solvency ratios, while the dependent variable in the form of Investment Opportunity Set (IOS). The company studied is a manufacturing company listed on the Indonesia Stock Exchange with a 3 year research period from 2008-2010. The number of samples used as many as 134 companies. The results of the partial regression testing shows that in the start-up stage of the activity ratio is only significant influence on the IOS, whereas in the early stages of expansion of liquidity and activity ratios only a significant influence on IOS. At the final stage of expansion, maturity, and decline in none of the financial ratios in this study that significantly influence the IOS.